The Effect of Effectiveness, Accessibility, and Ease of Service of Digitalized Sharia Banking Services from BSI Mobile to BYOND by BSI on CustomerSatisfaction at The Gandapura Branch Office - Wardiyati Wardiyati; Maryam Maryam; Cut Sukmawati; Ferizaldi Ferizaldi; Teuku Zulkarnaen (Sebatik, 2026)
This study aims to determine how the effectiveness, accessibility, and ease of service affect customer satisfaction with the BYOND by BSI application at BSI KCP Gandapura. This study was motivated by the author's observation that the usage rate of the BYOND by BSI application among KCP Gandapura customers is still low, as reflected in the perception that BYOND is not yet able to provide a better service experience than BSI Mobile. Customers are also reluctant to switch because the BYOND application is considered ineffective, often experiences technical problems, is difficult to access at certain times, and has a display and features that are not yet fully user-friendly. This study used a quantitative method, where the data source used was primary data obtained by distributing questionnaires to Gandapura KCP customers who were BYOND by BSI users. The data analysis technique used was multiple linear regression analysis using SPSS software. The results showed that the effectiveness, accessibility, and ease of service partially had a positive and significant effect on customer satisfaction with the BYOND by BSI application at KCP Gandapura. Then, the simultaneous test results showed that effectiveness, accessibility, and ease of service also had a significant effect on customer satisfaction with the BYOND by BSI application at KCP Gandapura.